Experimental and numerical studies on the static and the dynamic behaviors of embedded cable support (ECS) glass facade system. (1st January 2019) - Wang, Yuanqing; Wang, Zongyi; Xu, Kang; Shi, Yongjiu; Du, Xinxi
Highlights: The sealing of adjacent double IGUs has little effect on the structure. The structural deflection is the controlling factor for ECS glass facades. Preloads on cables have a significant effect on the static and the dynamic behaviors of ECS glass facades. The effects of glass panel thickness and cable diameter on the structure are relatively small. Abstract: Embedded cable support (ECS) glass facades are increasingly used in architectures, due to their good-looking appearance. In order to study the static and the dynamic behaviors of ECS glass facades, static and dynamic loading tests are carried out. The structural deflections, the axial forces of cables, and the natural frequencies under various test conditions are measured. Two finite element (FE) models are established in ABAQUS and calibrated by the test data. A parametric study is conducted to discuss the effects of preload, glass panel thickness, and cable diameter on the static and the dynamic behaviors of ECS glass facades. The results show that the sealing of adjacent insulated glasses has little effect on the structure. The structural deflection is the controlling factor for ECS glass facades, while the Mises stresses on the glasses are fairly low. The discrepancy of the results obtained from the two FE models is small. Preloads on cables have a significant effect on the static and the dynamic behaviors of ECS glass facades, whereas the effects of glass panel thickness and cable diameter on the structure are relatively small.